Factors affecting intention to continue playing an online game: the role of competition, challenge, competence, relationship, and usefulness of the game - Tata Wilia, Tri (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
Advances in device and communication technology have transformed gaming, with gamification significantly motivating users through game elements. Mobile apps increasingly use gamification to boost participation, yet there is limited evidence on how to attract and retain users effectively. This study identifies factors influencing players' intention to continue playing online games in Indonesia, focusing on competition, challenge, competence, social relationships, and usefulness. A survey involving 100 active players has been conducted, and data are being analyzed using SPSS. Initial findings reveal that among the examined factors, challenge significantly influences players’ intention to continue playing. Improved internet conditions in Indonesia are enhancing the gaming experience. The findings aim to provide insights for app and game developers to design effective player retention strategies, bridging the gap in understanding user engagement in mobile gaming and contributing to more engaging and sustainable gaming experiences for players in Indonesia. These results contribute to an ethical and sustainable digital marketing ecosystem in Indonesia by guiding developers to implement responsible gamification strategies that enhance long-term user engagement and trust.